The Drug Alphakalcidol Effectiveness in Osteoporosis in Patients with Systemic Sclerodermia - Masuda.B Kasimova; Khulkar B.Makhamatkhojaeva; Shakhlo B.Kakhkharova; Mukhayyo. A. Akhmadjonova (Zien Journals, 2022)
According to the WHO, this metabolic disease of the skeleton belongs to the leading non-infectious human pathologies after cardiovascular, oncological and diabetes mellitus. The article presents the results of studying the frequency of reducing bone mineral density and its relationship with traditional risk factors and clinical parameters, the effectiveness of the drug alfaphorcal (alfacalcidol) in complex treatment in 40 patients with systemic scleroderma with osteoporosis and osteopenia. According to ultrasound osteodensitometry, osteoporosis and osteopenia are a frequent complication of systemic scleroderma and are detected in 57.5% of patients. The incidence of osteoporosis in this disease is much higher with a long course of the disease and menopause. In patients with systemic scleroderma with osteoporosis, alfacalcidol at a dose of 0.5-1.0 μg per day leads to a significant reduction in bone pain, normalization of bone remodeling processes, and an increase in bone strength.
Keywords: patients; osteoporosis; bone mineral density; vitamin D